Multi-course OSCE experience 2025: simulating real-world pharmacy practice - Noordin, Zakiah Mohd; Nik Mustaffa Shapri, Nik Aisyah Najwa; Jamal, Janattul Ain; Jamludin, Nurul Ashikin; Sha’ari, Mohammad Suhaidi; Ibrahim, Norkasihan (Faculty of Pharmacy, 2025)
he Faculty of Pharmacy recently concluded a highly intensive series of Objective Structured Clinical Examinations (OSCEs) from 1st to 9th July 2025 involving 362 third and fourth year pharmacy students, marking a critical milestone for students across five advanced courses: PHC635 (Introduction to Clinical Pharmacy), PHC671 (Applied Therapeutics in Infectious Diseases and Neoplastic Disorders), PHC690 (Applied Therapeutics in Neurology, Immunology, Musculoskeletal System and Psychiatric Disorders), PHC691 (Applied Therapeutics In Gastrointestinal, Renal And Endocrine Disorders), and PHC692 (Applied Therapeutics in Cardiovascular and Pulmonary Disorders). These rigorous assessments are strategically designed to mirror the clinical and ethical challenges students will face during their upcoming Provisional Registered Pharmacist (PRP) training, solidifying UiTM’s commitment to producing practice-ready graduates.